Practice and Impact of Hair Dyeing; A Local Study - Dhafiri, Mahdi Al; Al Furaikh, Bashayer; Aljasir, Abdulelah; Alsubaie, Thamer; Al Dandan, Abdulelah; Alfalah, Renad; Albahar, Sarah (International Journal of Innovative Research in Medical Science, 2022)
Background: Hair dying has become a common practice among men and women. However, hair dye can be associated with several adverse effects varying from mild to severe reactions. Therefore, the study's main objective was to assess public practice, perception, and experienced complications of hair color treatments in Al-Ahsa region in Saudi Arabia. Methodology: A cross-sectional study was conducted on 355 male and female subjects among a single city population in Saudi Arabia; An online questionnaire was distributed to male and female subjects to evaluate the practice and impact of hair color usage. The questionnaire constituted three sections: biographical data, dye usage attitude, and awareness and knowledge about dye and its effects. Data were analyzed using descriptive analysis using Statistical Package for the Social Sciences (SPSS) v22. Results with a P value less than 0.05 were considered statistically significant. Results: Among 355 participants, 212 (59.7%) reported using hair dyes. The age of hair dye users averaged 36.1 ± 12.9 years old. The majority of dye users were females, 165 (77.8%). Most of them (29.2%) started using hair dyes at 20-25 years old. The frequency of dye usage, 91 (42.9%) dye their hair once a year. Additionally, 109 (51.4%) of subjects dye their hair by themselves at home. Hair colors have been used for various reasons, and the most common is to disguise grey hair and look younger, 97 (45.8%). 166 (78.3%) participants believe that non-chemical or herbal hair dyes are safer than chemical ones. Moreover, hair dye-caused side effects in 42 (19.8%) participants, with itching being the most common side effect (47.6 %). Conclusion: Our study found that hair dyeing is widely used for different purposes, and inappropriate beliefs and practices were detected among participants. Health education on hair-dying products must be improved to enhance the public's awareness of ingredients and side effects. Furthermore, an informative tool designed by experts will help individuals use hair coloring products safely and appropriately.